Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi, Dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja Instansi Pemerintah - Putri Dwi Maulidya; Ika Nur Azmi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to analyze the effect of budget target clarity, accounting control, and reporting system on the performance accountability of government agencies/institutions in the Work Units within the Ministry of Law and Human Rights of West Kalimantan. Performance accountability of government agencies refers to the responsibility for actions and programs implemented by the government. The research method is quantitative, using questionnaires sent to respondents. The research sample included 50 respondents from 14 work units at the Ministry of Law and Human Rights of West Kalimantan, selected using the purposive sampling method. Data was analyzed using multivariate regression analysis through SPSS v25 software. The study's results stated that budget target clarity and accounting control had no significant impact on performance accountability in the work units of the Ministry of Law and Human Rights of West Kalimantan. However, the reporting system had a substantial effect on the performance accountability of government agencies in work units within the Ministry of Law and Human Rights of West Kalimantan.